Ancient China and its enemies : the rise of nomadic power in East Asian history - Di Cosmo, Nicola, 1957- (Cambridge University Press, 2002)
Relations between Inner Asian nomads and Chinese are a continuous theme throughout Chinese history. By investigating the formation of nomadic cultures, by analyzing the evolution of patterns of interaction along China's northern frontiers, and by exploring how this interaction was recorded in early Chinese historiography, this book explores the origins of the cultural and political tensions between these two civilizations through the first millennium BC. The main purpose of the book is to analyze ethnic, cultural, and political frontiers between nomads and Chinese in the historical contexts that led to their formation, and to look at cultural perceptions of 'others' as a function of the same historical process. Based on both archaeological and textual sources, this book also introduces a new methodological approach to Chinese frontier history, which combines extensive factual data with a careful scrutiny of the motives, methods, and general conception of history that informed the Chinese historian Ssu-ma Ch'ien.